Improving Sales Performance Through Shapping Ambience Interaction - Dian Triyani; Elisabeth Rotua Simamora (Lembaga Riset dan Inovasi Al-Matani, 2026)
Despite the recognized importance of relationship capability in improving salesperson performance, previous studies have reported inconsistent findings regarding its direct contribution to sales outcomes. This study addresses this gap by proposing shaping ambience interaction as a mediating mechanism that explains how relationship capability is translated into superior salesperson performance. Drawing on Service-Dominant Logic and*Interaction Theory, this study develops and empirically tests a comprehensive model linking relation capability, shaping ambience interaction, sales adaptiveness, sales innovativeness, and sales performance. Data were collected from 400 pharmaceutical salespeople in Indonesia using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS. The results demonstrate that relation capability significantly enhances shaping ambience interaction, which subsequently improves salesperson performance both directly and indirectly through sales adaptiveness and sales innovativeness. Among the proposed relationships, shaping ambience interaction emerged as the central mechanism connecting relational capability with salesperson outcomes, while sales adaptiveness exerted a stronger influence on performance than sales innovativeness. These findings extend Service-Dominant Logic and Interaction Theory by introducing shaping ambience interaction as a key interaction-based capability that bridges relational resources and salesperson performance. The study also provides practical implications for pharmaceutical companies seeking to strengthen sales effectiveness through relationship-oriented capability development and customer-centered interaction strategies.